Silver nanoparticles do not influence stem cell differentiation but cause minimal toxicity. (August 2012) - Samberg, Meghan E; Loboa, Elizabeth G; Oldenburg, Steven J; Monteiro-Riviere, Nancy A
Aims: To evaluate the toxicity and cellular uptake of both undifferentiated and differentiated human adipose-derived stem cells (hASCs) exposed to silver nanoparticles (Ag-NPs), and to assess their effect on hASC differentiation.Materials & methods: hASC were exposed to 10- or 20-nm Ag-NPs at concentrations of 0.1, 1.0, 10.0, 50.0 and 100.0 µg/ml either before or after differentiation down the adipogenic or osteogenic pathways.Results: Exposure of hASC to either 10- or 20-nm Ag-NPs resulted in no significant cytotoxicity to hASC, and minimal dose-dependent toxicity to adipogenic and osteogenic cells at 10 µg/ml. Each of the hASC, adipogenic and osteogenic cells showed cellular uptake of both 10- and 20-nm Ag-NPs, without causing significant ultrastructural alterations. Exposure to 10- or 20-nm Ag-NPs did not influence the differentiation of the cells, and at antimicrobial concentrations of Ag-NPs resulted in a minimal decrease in viability.Conclusion: The biocompatibility of Ag-NPs with both undifferentiated and differentiated hASC establishes their suitability for incorporation into tissue-engineered graft scaffolds, for the prevention of bacterial contamination upon implantation. Original submitted 28 September 2011; Revised submitted 15 November 2011; Published online 14 May 2012